MR imaging of urinary bladder cancer for T‐staging: A review and a pictorial essay of diffusion‐weighted imaging. Issue 6 (14th July 2014) - Takeuchi, Mitsuru; Sasaki, Shigeru; Naiki, Taku; Kawai, Noriyasu; Kohri, Kenjiro; Hara, Masaki; Shibamoto, Yuta
Abstract : Treatment decisions for bladder cancer patients are mainly based on the depth of bladder wall invasion by the tumor. In this article, we review the conventional MRI and exhibit a recently emerged diffusion‐weighted imaging (DWI) of urinary bladder cancer for T‐staging. We discuss limitations of conventional MRI, scanning protocols of DWI, normal pelvic findings on DWI, determination of T‐stage using DWI, and pitfalls of DWI. DWI provides high contrast between bladder cancer and background tissue because the cancer shows markedly high SI. DWI has high sensitivity for detecting the stalk seen in stage Ta or T1. An inflammatory change or fibrosis surrounding the tumor mimics the invasion of bladder cancer on T2‐weighted imaging or enhanced MRI and could lead to over‐staging, but DWI could differentiate them clearly because these benign changes do not show high SI on DWI. DWI is also useful for detecting ureteral, urethral, and prostatic extension by means of the urethra. DWI provides more accurate information on the extent of bladder cancer and contributes to determination of the treatment strategy. J. Magn. Reson. Imaging 2013;38:1299–1309. © 2013 Wiley Periodicals, Inc.